A Simple Cocyclic Jacket Matrices. (28th July 2008) - Lee, Moon Ho; Feng, Gui-Liang; Chen, Zhu
Abstract : We present a new class of cocyclic Jacket matrices over complex number field with any size. We also construct cocyclic Jacket matrices over the finite field. Such kind of matrices has close relation with unitary matrices which are a first hand tool in solving many problems in mathematical and theoretical physics. Based on the analysis of the relation between cocyclic Jacket matrices and unitary matrices, the common method for factorizing these two kinds of matrices is presented.